The Effectiveness of Combination of Health Education and Stress Management on Blood Pressure in Patients with Hypertension - Wahyu Dini Candra Susila; Nurwahidah; Wahyu Dini Metrikayanto (Jurnal Kesehatan dr. Soebandi, 2024)
Hypertension is an important health problem that the public needs to be aware of, because hypertension is also known as the silent killer. Hypertension treatment is lifelong so it needs to be combined with non-pharmacological treatment, such as the combine intervention of health education, deep breath relaxation, and progressive muscle relaxation.  Pharmacological management aims to reduce complications and prevent death by achieving and maintaining normal blood pressure. The purpose of this study was determining the effectiveness of the combination of health education, deep breath relaxation, and progressive muscle relaxation in reducing blood pressure. This study combines health education with deep breathing relaxation and progressive muscle relaxation. This study used a Pre-Experimental Design research design with One Group Pretest-Posttest Design. The sampling technique used non-probability sampling technique, namely accidental sampling. The sample taken was 17 people. Respondents were selected using inclusion and exclusion criteria. The data obtained was then analyzed using the dependent t-test. This study covers the characteristics of respondents consisted of age, gender, education and duration of illness. The results of the t test for measuring blood pressure (pre and post), both systolic and diastolic, showed a p-value <0.05 (0.000). There is a reduction in systolic and diastolic blood pressure after being given a combination of education and stress management interventions: progressive muscle relaxation and deep breath relaxation. The conclusion in this study is that the combination of education and stress management in people with hypertension has an influence on patient blood pressure.